Interprofessional learning readiness among medical students in International Islamic University Malaysia using readiness for interprofessional learning scale inventory - Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim; Yaacob, Muhamad Yusadlan; Manaf, Ahmad Syakir; Ridzuan, Mohd Hafizi (2018)
EﬀecCve interprofessional learning (IPL) is a vital component in preparing an individual health professional students for future collaborative healthcare practice. Studies have shown that a multidisciplinary healthcare team can provide better treatment outcomes and quality care for patients. 1